Why feminist epistemology matters in education and educational research - Vendramin, Valerija (Šolsko polje, 2012)
The starting point of this contribution is feminist epistemology and above all its influential concept of situated knowledge (as developed above all by D. Haraway in science). Their importance for the field of education is investigated as well as the presentation of certain fundamental postulates highlighting above all the socially embedded knowing subject whilst paying attention to the practice of feminist objectivity. Furthermore, the hidden curriculum, which can be taken to be an epistemological topic, is brought to the forefront, on the basis of which, the range of the approach taking into consideration situated knowledge is illustrated. By focusing on the category of gender (but not excluding other social axes of domination) a common sense approach is taken, which prevents an insight into the specificity of context and self-reflection on how we reached understanding, what the "tacit" cultural premises are and which domination relations help define our views in education.
Keywords: education; vzgoja in izobraževanje; spol; gender; kurikulum; curriculum; feminist epistemology; feministična epistemologija; pedagoško raziskovanje; situated knowledges; educational research